PASSENGER TRANSPORTATION SEA TRANSPORTATION SERVICES IN PANDEMY - Ahmad; Agus Setiawan; edikurniawan (Fakultas Sains dan Teknologi Universitas Karimun, 2021)
The Ministry of Transportation (Kemenhub) issued a Minister of Transportation Regulation Number 18 of 2020 concerning Transportation Control in the context of Preventing the Spread of Covid-19. broadly regulates three things, namely: transportation control for the entire region, transportation control in areas designated as Large-Scale Social Restrictions (PSBB), and transportation control for homecoming activities in 2020. Includes public and private vehicle passengers, operators of transportation facilities and infrastructure both in land, rail, sea and air transportation. The method used in this research is literature study, which is all the efforts made by the researcher to gather information that is relevant to the topic or problem to be or is being researched. This information can be obtained from scientific books, research reports, scientific essays, theses and dissertations, regulations, statutes, yearbooks, encyclopedias, and other written and electronic sources. The following conclusions are as follows: The condition of the available facilities now, Sea Transportation Passenger Transport Services during the Pandemic, both dock infrastructure and stacking fields, need to develop port infrastructure and health protocols to anticipate additional passenger flows. Another effort that has been made is by implementing social distancing and work from home (WFH) recommendations for related parties in the Indonesian maritime world. Keywords: Service, sea transportation, pandemic